Exciton recombination in spontaneously formed and artificial quantum wells AlxGa1‐xN/AlyGa1‐yN (x<y∼0.8). Issue 5 (29th March 2016) - Toropov, A. A.; Shevchenko, E. A.; Shubina, T. V.; Jmerik, V. N.; Nechaev, D. V.; Pozina, G.; Bergman, P.; Monemar, B.; Rouvimov, S.; Ivanov, S. V.
Abstract: We report on photoluminescence (PL) spectroscopy and electron microscopy studies of an AlGaN quantum well (QW) structure grown by molecular beam epitaxy under metal‐rich conditions with substrate rotation. Both techniques reveal unintentional formation within the AlGaN barriers of a quasiperiodic structure of thin Ga‐rich layers, whose period is controlled by both the substrate rotation rate and the AlGaN growth rate. These compositional modulations act as 1‐3 monolayer thick QWs emitting below 250 nm with an internal quantum efficiency (IQE) as high as ∼30% at room temperature under weak excitation. Variational calculations of the QW exciton properties indicate that the observed high IQE can result from strong three‐dimensional localization of the excitons confined in the narrow QWs. (© 2015 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)